A middle east systematic review and meta-analysis of bacterial urinary tract infection among renal transplant recipients; Causative microorganisms. (November 2020) - Behzad, Dadfar; Hakimeh, Akbari; Hossein, Ranjbar; Khaledi, Azad
Abstract: UTI has been reported as the most prevalent infectious complication after-kidney transplantation. This study aimed to evaluate the bacterial urinary tract infection among renal transplant recipients, and causative microorganisms from the Middle East. We searched literatures reporting the prevalence of UTI, bacterial pathogens, and antibiotic resistance pattern from January 1, 2010–May 10, 2020 for patients with renal transplant recipients from the Middle East in international databases. Terms used were; "Urinary tract infection", "UTI", "bacterial pathogens", "bacterial infection", "renal transplant", "kidney transplant", post - renal transplant, "antibiotic resistance", "Middle East", Turkey, Iran, Jordan, Kuwait, Bahrain, Lebanon, United Arab Emirates, Qatar, Cyprus, Yemen, Iraq, Egypt, Palestine, and Syria. Data analyzed using CMA software. The prevalence of UTI among renal transplant recipients from the Middle East varied between 4.5 and 85%. The combined prevalence of UTI was reported by 37.9% (95% Cl: 28.3–48.5). The most prevalent organisms recovered from urine samples of patients with UTI were E. coli and Klebsiella with prevalence rate of 57.5%, and 15%, respectively. Also, Coagulase negative Staphylococcus (15%), and Enterococci (11.2%) were the most predominant among Gram positive microorganisms. The most resistance among Gram negative microorganisms belonged to Ceftazidime with frequency of 90% followed by Carbenicillin and Cephalexin with prevalence of 87.3%, and 84%, respectively. The effective antibiotic was Imipenem (15.2%). Regarding the high UTI rate in renal transplant recipients from the Middle East, and the significant presence of both Gram negative and Gram positive microorganisms as the most prevalent uropathogens after renal transplantation should be considered when selecting empirical antibacterial therapy. Highlights: The prevalence of UTI among renal transplant recipients from the Middle East varied between 4.5 and 85%. The combined prevalence of UTI was reported by 37.9% (95% Cl: 28.3–48.5). The most prevalent organisms recovered from urine samples of patients with UTI were E. coli (57.5%).